Kardec's spiritism, mental health and the production of scientific knowledge - Sales, Tiago Medeiros; Mota, Rosa Maria Salani; Macena, Raimunda Hermelinda Maia (Seven Editora, 2023)
Spirituality is a relevant field for science and a body of research shows its health benefits. In turn, spiritism presents itself as a theoretical-practical doctrine that can positively influence mental health. This narrative-integrative review carried out a search aiming at the scientific knowledge produced in the interface between spiritism and mental health. It was seen that, currently, institutional research centers, such as the Center for Research in Spirituality and Health (NUPES) and the Health, Spirituality and Religiosity Program (ProSER) are dedicated to this theme, in addition to areas of psychology, such as transpersonal and the anomalistic. It was also demonstrated that the spiritist proposal of “intimate reform” has a therapeutic inclination for the mind, with benefits evidenced in research on some specific spiritist activities, such as mediumistic meetings, passes and the study of the gospel and doctrine. In parallel, mediumship has been extensively researched, demonstrating itself as a legitimate human phenomenon, not invented, still to be better understood. DOI:https://doi.org/10.56238/alookdevelopv1-082